A participaç\~ao dos serviços nas cadeias globais de valor selecionadas - Rosana Curzel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The main objective of this study was to analyze the recent international trade database developed by the OECD, WTO and Unctad, which took into account the perspective of value added, unlike other bases that considers the gross data. From the initial focus of the service chain, it was found that these are strongly present in the automotive industry, followed by wood products, paper and publishing, and the chain of food, beverages and tobacco. Thus, the work consists of the presentation of the main indicators of fragmentation of production of these three chains, such as domestic value added embodied in gross exports, services industry value added embodied in gross exports, domestic value added embodied in foreign final demand, participation index in global value chains, index of the number of production stages and index of distance to final demand.
Keywords: F14; Y10; 330; global value chain (GVC); automotive chain; Trade in Value-Added (TiVA)